1992
DOI: 10.1016/0248-4900(92)90198-a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and supramolecular architecture of the cellulose‐protein fibrils in the tunic of the sea peach (Halocynthia papillosa, Ascidiacea, Urochordata)

Abstract: The cellulose-protein fibrils, which constitute by far the bulk of the fibrous fraction of the sea peach tunic (Halocynthia papillosa), were structurally and chemically characterized, either in situ or after extraction procedures, with the use of classical electron microscopy combined with diffraction contrast imaging and electron diffraction, histochemistry, affinity cytochemistry and chemical analysis. These fibrils exhibit a cross-sectional shape close to a parallelogram. The crystallites forming their core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 24 publications
2
56
1
1
Order By: Relevance
“…Thus, we can conclude that the TEMPO-mediated oxidation conditions that were used here do not have further hydrolytic treatment on the whiskers, whose lengths are determined by the initial hydrolytic treatment. Regarding the whisker width and their distribution, they are essentially close to those observed in the initial tunicate mantle (Van Daele et al 1992). Therefore, neither the hydrolytic treatment, nor the surface oxidation seems to have any thinning effect on the tunicin whiskers, in contrast with other solid-state treatments such as acetylation (Sassi and Chanzy 1995) or enzymatic digestion (Chanzy and Henrissat 1983).…”
Section: Chemical Characterization Of the Oxidized Cellulose Whiskersmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, we can conclude that the TEMPO-mediated oxidation conditions that were used here do not have further hydrolytic treatment on the whiskers, whose lengths are determined by the initial hydrolytic treatment. Regarding the whisker width and their distribution, they are essentially close to those observed in the initial tunicate mantle (Van Daele et al 1992). Therefore, neither the hydrolytic treatment, nor the surface oxidation seems to have any thinning effect on the tunicin whiskers, in contrast with other solid-state treatments such as acetylation (Sassi and Chanzy 1995) or enzymatic digestion (Chanzy and Henrissat 1983).…”
Section: Chemical Characterization Of the Oxidized Cellulose Whiskersmentioning
confidence: 72%
“…The tunicin whiskers have the section of truncated lozenges (Helbert et al 1998) that for simplification can be modeled as rectangles with average dimensions of long and short sides, respectively, L = 18.2 nm and l = 8.8 nm (Van Daele et al 1992;Terech et al 1999). In Figure 2, we show the representation of a model whisker and its orientation with respect to the section of the unit cell of cellulose Ib and its two lattice parameters a = 0.801 nm and b = 0.817 nm (Sugiyama et al 1991).…”
Section: Chemical Characterization Of the Oxidized Cellulose Whiskersmentioning
confidence: 99%
“…These bundles are randomly deposited on the tunic so as to give the analogue of "randomly oriented plywood" appearance. This makes it technically difficult to align the microfibrils and visualize their precise cross-sectional shapes: the only successful images obtained to date came from Halocynthia papillosa (Revol et al 1990, Daele et al 1992. Interestingly, these authors found a unique parallelogram which prompted us to speculate on the difference in the mode of crystallization between Ia-and Io-rich cellulose microfibrils.…”
Section: Introductionmentioning
confidence: 94%
“…Among the macromolecular supports used so far in biosensors, cellulose structures provide the best prerequisites because of polyfunctionality, supramolecular structure forming potential and due to their hydrophilic and biocompatible properties 1) . Examples may be found in nature too where linkages between cellulose or other polysaccharides with proteins, e. g., supramolecular structures of collagen or elastin and cellulose or polysaccharide-protein structures in the case of glycoproteins, lead to a stabilization of the protein conformation 2,3) . The aim of our structural design studies consists in a novel type of cellulose derivatives corresponding to the above requirements of a transducer building block.…”
Section: Introductionmentioning
confidence: 99%